Patent suspension on the COVID-19 vaccine in Indonesian patent law perspective - Vania Lutfi Safira Erlangga; Anisa Izzati; Budi Agus Riswandi; Mahrus Ali (Cogent Social Sciences, 2023)
Vaccination patent is associated with exclusive rights that restrict the production, use, and sale of inventions by third parties for a specific period. This factor contributes to the high cost of vaccines, making it challenging to access vaccines in many underdeveloped nations such as Indonesia. The urgency for faster vaccine distribution during the COVID-19 pandemic further highlights this issue. However, the patent provisions of the Trade-Related Aspects of Intellectual Property Rights (TRIPs Agreement) may exacerbate the unequal distribution of vaccines worldwide. This study analyzes the implementation of the flexibility feature of the TRIPs Agreement, and Doha Declaration contained in Law Number 13 of 2016 respecting Patent to achieve a pandemic-free era. It is also necessary to examine the Indonesian patent rules and regulations, the TRIPs Agreement, the Doha Declaration, and other legal documents to examine these issues. The results showed that the patent rules and regulations have adopted flexibility under the TRIPs Agreement and the Doha Declaration. However, the effect on the country’s sluggish pharmaceutical supply chain has not been improved. A patent suspension system on a global scale is required to hasten the transition to a pandemic-free period since the feature of flexibility cannot handle the slow pace of vaccine procurement. The patent suspension system can be implemented through international agreements, such as the Patent Suspension Proposal filed by South Africa and India in October 2020. The suspension is crucial to accelerate the equitable distribution of vaccines and reduce their price.